Injuries and Physical Fitness Potential in Futsal Players - Suryadin, Tatang; Raharja, Didik Subekti Prawira; Fauzi, Riza Sukma; Sahudi, Udi; Prabowo, Indra; Rahmadi, Jaya Agung; Ghifari, Ababil Al (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
As a sport that involves physical contact (body contact), futsal carries a significant risk of injury for its players. A futsal athlete may sustain an injury during practice, competition, or after either activity. The average level of physical fitness among rookie futsal players in Majalengka Regency is 250.00, and their average risk of sports injuries is 33.12. The number derived from correlation analysis is -0.607529. The strong relationship category includes this value. The likelihood of damage is thereby reduced with increasing physical fitness. One of the things that helps reduce the chance of an athlete getting hurt is fitness.